Pengaruh Mental Practice Terhadap Penampilan Atlet Pemula Pencak Silat Kategori Seni Tunggal Baku Jurus Tangan Kosong (di SDN Kejawen Putih II Surabaya) - Mungit Soedianto, (Pendidikan Sekolah Dasar, 2010)
Johansyah lubis declare a single category is a category of the championship which featured a martial arts fighter demonstrate expertise in a single raw stance is correct, accurate, and steady, full of inspiration with his bare hands and weapons. Program is a unity of mental practice program overall. So who should regulate trainer schedules. A good martial arts training should be focused on physical aspects, techniques, strategies and mentality of a champion. So with the existence of mental practice will help athletes to improve performance. Mental visualization is a technique that we can use to construct our performance internally, as we want or expect, either in practice or in the description above championship. Based on the title of this paper is "Effect of mental practice on performance of martial art athletes raw single stance art category empty-handed. Typical characteristics of athletes who experience mental disorders at the time following the championships are: nervous, anxious, nervous, not concentrating, forgetfulness, heart pounding-pounding, and lack of confidence. This study basically is to find out whether there is influence of mental practice on performance of novice athletes singular art of Pencak Silat category raw empty-handed stance. In accordance with the problems and hypotheses that the authors propose to use statistical data analysis with quantitative approach. Based on the calculation results of Karl Pearson correlation test and Spearman correlation test. observations on the assessment by the jury of five single raw art empty-handed stance obtained the same significant value is 0.002 <0.01 hence H0 is rejected, while H1 is accepted it means there is a positive influence of mental practice on the performance art of martial arts athletes beginner raw single empty-handed stance.